Community-Based Risk Factor Surveillance and Its Role in Prevention of Non-Communicable Diseases in Padang: A Qualitative Study - Abdiana Abdiana; Masrul Masrul; Hardisman Hardisman; Najirman Najirman; Rizanda Machmud; Firdawati Firdawati; Yantri Maputra; Musfardi Rustam (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
The rise in non-communicable diseases (NCDs) is driven by risk factors such as smoking, physical inactivity, low consumption of fruits and vegetables, and alcohol use. Community-based surveillance of these risk factors is essential for NCD prevention; however, the availability and use of accurate data remain limited in many regions. Therefore, research is needed to enhance both the quality and utilization of surveillance data in NCD prevention efforts. This study aims to examine community-based risk factor surveillance activities and their role in preventing NCDs in Padang. A qualitative approach using a phenomenological method was employed. Research informants included individuals responsible for NCD programs at community health centers, health cadres, and members of the productive-age population in Padang in 2024. Informants were selected through purposive sampling. Data were primarily collected via in-depth interviews guided by a structured interview protocol. Interview transcripts were analyzed using an interactive analysis model, which included data reduction, data presentation, and conclusion drawing/verification. Findings indicate that risk factor data collection at integrated health posts was conducted both manually and electronically, with data entered into the Ministry of Health's Asik application. Data processing and analysis were performed using the Asik application, with descriptive interpretations presented in tables and diagrams. Dissemination of risk factor information occurred through mini-workshops, although not all stakeholders were involved. Surveillance results were used to inform NCD prevention programs through counseling and community outreach. Overall, community-based risk factor surveillance data were collected manually and electronically via the Asik application, analyzed descriptively, and disseminated through workshops and follow-up activities supporting NCD prevention. The study highlights the need to improve the quality and use of community-based surveillance data, increase stakeholder engagement, evaluate intervention effectiveness, and assess the impact of surveillance applications on data processing and ongoing monitoring of NCD risk factors. Keyword: Surveillance, Risk Factors, Prevention, Non-Communicable Diseases.